PROBLEMATIKA PENDIDIKAN PESANTREN DALAM MENINGKATKAN INSAN AKADEMIS BERKUALITAS DI ERA GLOBAL-MULTIKULTURAL - surahman, buyung (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2018)
This scientificwork outlines the obstacles facing pesantren education in improving quality academic people in the global-multicultural era. Pesantren, global currents can cause paradox or symptoms of counter-morality, and so does the pattern of life in the west, even greatly affect the moral decay, moral and human behavior. With this condition, the influence is very large on human life both physical and spiritual. Thus pesantren education faced various challenges with the development of education models in the era of globalization implemented by members of the community, such as system problems, human resource problems, curriculum development. Therefore, in an effort to improve quality academic humanity in global-multicultural era, pesantren have problems to explore all the resources they have, because influenced by pesantren education is less concern to the problem, human resource problem, strong influence of western culture in domination and imperialisation of information, as well as the current culture of globalization can lead to paradox or symptoms of counter-morality. With this problem, pesantren is time to devote all the power, effort and ability to always innovate, finding something new can help his life for the better. If the pesantren does not dig all his skills then he will be left behind by the ever-evolving era.